Status of Mercury and Imp: Two Monte Carlo Transport Codes Developed Using Shared Infrastructure at Lawrence Livermore National Laboratory - Pozulp Michael; Beck Bret; Bleile Ryan; Brantley Patrick; Dawson Shawn; Gentile Nick; Gonzalez Evan; Grondalski John; Lambert Michael; McKinley Michael; O’Brien Matthew; Procassini Richard; et al. (EPJ Nuclear Sciences & Technologies)
The Monte Carlo Transport Project at Lawrence Livermore National Laboratory develops two Monte Carlo transport codes used in production by a sizable internal user community. Mercury is a Monte Carlo particle transport code used to model the interaction of neutrons, gammas, and light ions with a material. Imp is an implicit Monte Carlo thermal x-ray photon transport code used to model the interaction of x-ray photons with a material. This paper describes the two codes and highlights recent developments.